2017
DOI: 10.1080/19420862.2017.1338222
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of highly concentrated antibody solution - A toolbox for the description of protein long-term solution stability

Abstract: High protein titers are gaining importance in biopharmaceutical industry. A major challenge in the development of highly concentrated mAb solutions is their long-term stability and often incalculable viscosity. The complexity of the molecule itself, as well as the various molecular interactions, make it difficult to describe their solution behavior. To study the formulation stability, long- and short-range interactions and the formation of complex network structures have to be taken into account. For a better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 76 publications
1
35
0
Order By: Relevance
“…Potential structure-destabilizing residues may be identified based upon the crystal structure of the antibody or by molecular modeling in certain cases, and the effect of the residues on antibody stability may be tested by generating and evaluating variants harboring mutations in the identified residues. One of the ways to increase antibody stability is to raise the thermal transition midpoint (T m ) as measured by differential scanning calorimetry (DSC), differential scanning fluorimetry (DSF), or thermal transitions [280][281][282][283][284]. In general, the protein T m is correlated with its stability and inversely correlated with its susceptibility to unfolding and denaturation in solution and the degradation processes that depend on the tendency of the protein to unfold [285].…”
Section: Stabilitymentioning
confidence: 99%
“…Potential structure-destabilizing residues may be identified based upon the crystal structure of the antibody or by molecular modeling in certain cases, and the effect of the residues on antibody stability may be tested by generating and evaluating variants harboring mutations in the identified residues. One of the ways to increase antibody stability is to raise the thermal transition midpoint (T m ) as measured by differential scanning calorimetry (DSC), differential scanning fluorimetry (DSF), or thermal transitions [280][281][282][283][284]. In general, the protein T m is correlated with its stability and inversely correlated with its susceptibility to unfolding and denaturation in solution and the degradation processes that depend on the tendency of the protein to unfold [285].…”
Section: Stabilitymentioning
confidence: 99%
“…Both the inherent protein fold stability and self-association between protein molecules contribute to physical instability 3,4 . Whether reversible or irreversible, self-association can lead to undesirable solution behaviour such as phase separation 5 or aggregation 6,7 which can limit, or even abrogate, the development of a promising biopharmaceutical lead .…”
mentioning
confidence: 99%
“…Higher protein concentrations also seem to increase the viscosity of solutions, which itself may increase the aggregation potential of proteins by enhancing protein-protein interactions and self-association. 27,62 This concentration-dependent tendency to aggregation is an increasing concern considering the extended use of subcutaneous administration of mAbs which require highly concentrated solutions. However, the real impact of high protein concentrations is complex, as can be seen, for example, in the work published by Hauptmann et al 63 where they showed that high concentrations increased smaller particles concentrations while decreasing bigger ones, whereas Nicoud et al 64 showed an increase in aggregation rate with concentration.…”
Section: Protein Structurementioning
confidence: 99%
“…71,72 Likewise, zeta potential can be a good indicator of the surface charges that may lead to electrostatic and van der Waals interactions. 62 Temperature mAbs, like other therapeutic proteins, can be exposed to temperature variations during their processing, storage, and transportation. 24,49 High temperatures can perturb the native protein conformation to a sufficient degree to promote aggregation, but it starts at temperatures well below the equilibrium melting temperature (Tm) of the protein.…”
Section: Protein Structurementioning
confidence: 99%